The Catalytic Alkylative Desymmetrization of Anhydrides in a Formal Synthesis of Ionomycin - Oberg, Kevin M.; Cochran, Brian M.; Cook, Matthew J.; Rovis, Tomislav (Synthesis, 2018)
The catalytic desymmetrization of anhydrides with zinc reagents provides access to deoxypolypropionate and polypropionate synthons. A synthesis of ionomycin was pursued in which three of the four fragments were assembled using this methodology. Two of the strategies (enol silane/oxocarbenium coupling and reductive cyclization) were not successful at installing the C23 stereocenter, but this stereochemical issue was overcome through a reduction/SN2 approach. In addition to the synthesis of a protected diastereomer of ionomycin, the synthesis of a C17–C32 fragment constitutes a formal total synthesis.
Keywords: total synthesis; rhodium; enantioselective synthesis; anhydride desymmetrization; diastereoselectivity